2017
DOI: 10.1002/ddr.21377
|View full text |Cite
|
Sign up to set email alerts
|

Morin Inhibits Proliferation, Migration, and Invasion of Bladder Cancer EJ Cells via Modulation of Signaling Pathways, Cell Cycle Regulators, and Transcription Factor‐Mediated MMP‐9 Expression

Abstract: Preclinical Research Previous studies have shown that morin exerts diverse pharmacological activities. In this study, we investigated the inhibitory activity of morin on bladder cancer EJ cells. Morin significantly inhibited EJ cell proliferation, which was related to the G1-phase cell cycle arrest together with the reduced expression of cyclin D1, cyclin E, CDK2, and CDK4 via increased expression of p21WAF1. Morin also increased ERK1/2 phosphorylation and decreased JNK and AKT phosphorylation without altering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 26 publications
0
23
0
Order By: Relevance
“…In vitro morin protects from apoptosis of renal proximal tubular cells (HK-2 cell line) caused by endoplasmic reticulum stress [31]. Recent studies also suggest that morin may increase anticancer activity of some conventional anticancer agents, e.g., fludarabine, inhibiting low molecular weight protein tyrosine phosphatase (LMW-PTP) [32], and may inhibit proliferation, migration, and invasion of EJ cells of bladder cancer via many different intracellular mechanisms [33].…”
Section: Discussionmentioning
confidence: 99%
“…In vitro morin protects from apoptosis of renal proximal tubular cells (HK-2 cell line) caused by endoplasmic reticulum stress [31]. Recent studies also suggest that morin may increase anticancer activity of some conventional anticancer agents, e.g., fludarabine, inhibiting low molecular weight protein tyrosine phosphatase (LMW-PTP) [32], and may inhibit proliferation, migration, and invasion of EJ cells of bladder cancer via many different intracellular mechanisms [33].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, modulating activity of cell cycle regulators may be a good strategy for inhibiting PDGFmediated VSMC proliferation. Although morin displays anti-proliferative activity against both normal hepatocytes (MadanKumar et al 2014) and cancerous cells (Shin et al 2017;Zhang et al 2018), little has been reported on the cell cycle distribution profile mediated by morin in VSMCs. Therefore, we investigated cell cycle phase distribution using flow cytometry with morin-treated VSMCs.…”
Section: Discussionmentioning
confidence: 99%
“…This dietary flavonol significantly downregulates the expression levels of genes involved in EMT in ovarian cancer cells (Nowak et al, 2020). Morin has the ability to suppress migration and invasion of bladder cancer EJ cells by decreasing the expression level of MMP-9 through inhibition of NF-κB (Shin et al, 2017). Morin treatment effectively inhibits the migration and invasion of MCF-7 human breast cancer cells by suppressing Akt pathway and downregulating the expression of MMP-9, MMP-7, urokinase plasminogen activator (uPA), uPA receptor (uPAR), and fibronectin (Lee, Nam, et al, 2020) (Table 2).…”
Section: Inhibition Of Cancer Cell Migration and Invasion And Antican...mentioning
confidence: 99%
“…Many polyphenolic compounds have been reported to repress NF-κB pathway in cancer cells, leading to the induction of apoptotic cell death and inhibition of cancer cell proliferation, migration, and invasion (Khan et al, 2020). Dietary morin has been found to remarkably inhibit the NF-κB signaling pathway in cancer cells (Shin et al, 2017;Zhang et al, 2018) (Figure 5). Morin has the potential to suppress the proliferation of human colorectal cells by inhibiting the NF-κB activity .…”
Section: Nf-κb Signaling Pathway and Anticancer Effects Of Morinmentioning
confidence: 99%